(untitled) (Transactions on Additive Manufacturing Meets Medicine, 2023)
Additive manufacturing (AM) has long been established in many industrial sectors. One particularly exciting field is medicine / medical technology. AM enables the production of patient-specific, individual implants, prostheses, orthoses, tissues, precision tools and much more. A variety of different technologies and materials are used to provide the best possible patient care. Regulatory requirements are high, but quality management is improving, especially in hospitals with point of care manufacturing. This presentation will give an overview of the many various use cases and show the latest developments with respect to needs, materials and manufacturing processes. AM is not only an important component in personalized medicine, but also helps to reduce costs and risks.